Okoljski učinki turizma in rekreacije - Cigale, Dejan (Geografski obzornik, 2004)
The Alps are one of the touristics most interesting and also most visited parts of the world. Because of that various impacts of tourism have special importance. The Alps are characterised by unique natural and socio-geographical features and pronounced environmental sensitivity. In the Slovenian Alps vast areas with rather moderate effects of tourism and recreation prevail. But in the most visited areas the number of visitors is of such extent, that increased influences of tourism are evident in impacts on all landscape components.
Keywords: Alpe; ekologija; ekološko ravnotežje; prosti čas; rekreacija; Slovenija; sonaravni razvoj; turistična geografija; turizem